The Influence of the Development of Information Technology on the Legal System in Indonesia - Hadi Purnomo (INFOKUM, 2023)
The increasingly rapid development of the world of information technology has resulted in legal relations in the midst of society which has given rise to various crimes and other legal activities that have not yet been regulated because the modes used are new modes of crime in the world of law. regarding these legal relationships in the world of technology. This research aims to determine the influence of technological developments on the criminal law system in Indonesia. This research is normative legal research with a statutory approach. The results of this research highlight the significant role of the Information and Electronic Transactions Law (UU ITE) in regulating and protecting security in cyberspace. The ITE Law not only creates a legal framework for electronic transactions, but also becomes an instrument for law enforcement against cybercrime. Nevertheless, implementation challenges in the field, increasing the capacity of law enforcement officials, and cross-sector collaboration remain the main focus in dealing with legal and technological complexity. This research highlights Indonesia's efforts to form a responsive and dynamic legal system, taking into account the values of Pancasila as the ideological foundation.